Association of early childhood abdominal circumference and weight gain with blood pressure at 36 months of age: secondary analysis of data from a prospective cohort study. Issue 7 (3rd July 2014) - Nowson, Caryl A; Crozier, Sarah R; Robinson, Siân M; Godfrey, Keith M; Lawrence, Wendy T; Law, Catherine M; Cooper, Cyrus; Inskip, Hazel M
Abstract : Objectives: To assess whether changes in measures of fat distribution and body size during early life are associated with blood pressure at 36 months of age. Design: Analysis of data collected from a prospective cohort study. Setting: Community-based investigation in Southampton, UK. Participants: 761 children with valid blood pressure measurements, born to women participating in the Southampton Women's Survey. Primary and secondary outcome measures: Anthropometric measurements were collected at 0, 6, 12, 24 and 36 months and conditional changes between the time points calculated. Blood pressure was measured at 36 months. Factors possibly influencing the blood pressure were assessed using linear regression. All independent variables of interest and confounding variables were included in stepwise multiple regression to identify the model that best predicted blood pressure at 36 months. Results: Greater conditional gains in abdominal circumference (AC) between 0–6 and 24–36 months were associated with higher systolic and diastolic blood pressures at 36 months (p<0.001). Subscapular skinfold and height gains were weakly associated with higher blood pressures, while greater weight gains between 0–6, 12–24 and 24–36 months were more strongly associated, but the dominant influences were AC gains, particularly from 0–6 to 24–36 months. Thus one SD score increases in AC between 0–6 and 24–36 months were associated with 1.59 mm Hg (95% CI 0.97 to 2.21) and 1.84 mm Hg (1.24 to 2.46) higher systolic blood pressures, respectively, and 1.04 mm Hg (0.57 to 1.51) and 1.02 mm Hg (0.56, 1.48) higher diastolic pressures, respectively. Conclusions: Conditional gains in abdominal circumference, particularly within 6 months of birth and in the year preceding measurement, were more positively associated with blood pressure at 36 months than gains in other anthropometric measures. Above-average AC gains in early childhood may contribute to adult hypertension and increased cardiovascular disease risk.